VEHICLE AUTOMATION-CONNECTED PEDESTRIAN RISK ASSESSMENT DEVICE (2020)
Systems and methods for alerting a pedestrian of the density of automated vehicles to non-automated vehicles in an area by broadcasting a visual signal representing a group mode status of automated vehicles travelling towards or within a roadway intersection. The group mode status may be broadcast as a percentage of automated vehicles to total vehicles or can be broadcast as a ratio of automated vehicles to non-automated vehicles on an external mode indicator of a subject automated vehicle. The visual signal may be broadcast as a pattern of lighting, a change in light intensity, a change in colors or a change in text. The group mode status may also be broadcast to a pedestrian equipped with a wireless device via vehicle-to-infrastructure communications. The group status may also be broadcast to and displayed on infrastructure component, such as a street light, display post, crosswalk sign, or building display configured to receive signals.